Ultrabroadband balun with 1:4 impedance transformation ratio using transmission‐line transformers. Issue 9 (September 2014) - Lee, H.; Gu, J.; Kwon, J.; Seo, M.; Ham, J.; Kim, H.; Yang, Y.
ABSTRACT This article presents an ultrabroadband balun with 1:4 impedance transformation ratio using transmission‐line transformers. The proposed ultrabroadband balun consists of one 1:1 transmission‐line transformer as a balun and two 1:4 transmission‐line transformers for impedance transformation. Each transmission‐line transformer is based on a coaxial line, which is wound around a ferrite core to extend the bandwidth to the lower frequency region. Experimentally optimized offset transmission lines are used to compensate for the phase imbalance characteristics at the high frequency band. The implemented ultrabroadband balun operates from 300 kHz to 400 MHz with a return loss of below 12 dB and an insertion loss of less than 1 dB. The magnitude and phase imbalance for the balanced signal output are both less than 0.5 dB and 2.0°, respectively. An outstanding relative bandwidth (the ratio of the highest frequency to the lowest frequency in the operational band) of 1330 was achieved. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1974–1978, 2014